The Correlation between SDL (Self-Directed Learning) Level and the Argumentative Writing Performance in EFL Classes - Vina Humaero (Sumber Belajar Sejahtera, 2026)
In EFL contexts, self-directed learning (SDL) is important for supporting writing development, particularly argumentative writing, which requires learners to generate ideas, organize arguments, and use evidence effectively. However, EFL learners often face difficulties in argumentative writing, especially in organization, coherence, and language use. Although previous studies have shown a positive relationship between SDL and general writing performance, limited research has focused specifically on the relationship between SDL and argumentative writing performance in higher education contexts. This study aimed to examine the correlation between SDL levels and students’ argumentative writing performance and to identify the distribution of SDL levels among EFL learners. The study employed an ex-post facto quantitative correlational design. The participants were 26 students from the English Education Program at the University of Mataram. Data were collected using an adapted 40-item Self-Rating Scale of Self-Directed Learning (SRSSDL) questionnaire and an argumentative writing test. Data were analyzed using SPSS version 25.0. The results showed that 61.5% of students had a moderate level of SDL, while 38.5% had a high level. The Pearson correlation analysis revealed a very strong and significant positive relationship between SDL and argumentative writing performance (r = .885, p < .01). This indicates that students with higher SDL levels tend to achieve better writing performance. It is suggested that future researchers investigate other factors influencing argumentative writing performance, such as critical thinking skills, writing motivation, and language proficiency, and explore SDL in different EFL contexts with larger samples.